Mobile information behavior measuring system (MIB_MeSys) - Abdul Rahman, Abd Latif; Arif, Zuraidah; Mohammed Ghazali, Asmadi (Universiti Teknologi MARA, Kedah, 2017)
Advance technology enable library offer their services through digital library providing electronic resources (Ebook, online database, exam papers, thesis, and others) and engage with user using social network platform (e.g.: Facebook, Blog, Youtube, etc). Some library even offer chat with librarian in order to meet the current needs where user can access library collection and services without going to physical library. With the variety of services that can be access through network, understanding user acceptance behavior is a good way to enhance library services to ensure user continuously use library services. The service that enables users to effectively employ electronic data by using an in-library network is also referred to as an "electronic library service”. The success of the electronic library services depends on the efficiency of the library system, acceptance and usage by their users. Therefore, it is crucial to investigate and understand not only its acceptance and usage, but also how and why it is being accepted and used. With this knowledge, better library system and information services can be offered to the users at large. The proposed Mobile Information Behavior Measuring System (MIB_MeSys) would help librarians and information professional in Malaysia in determine the level and factors affecting the continued use and roles of libraries. This proposed MIB_MeSys prototype were developed based on previous research onmodified UTAUT (Unified Theory of Acceptance and Use of Technology), SOUTAUT (Service Oriented Unified Theory of Acceptance and Use of Technology), NUTAUT (Nationality oriented Unified Theory of Acceptance and Use of Technology), Delone and Mclean’s Information Success Model and DLACU (Digital Library Acceptance and Continued Use). The proposed MIB incorporates information quality construct as independent variables and continued use of electronic library as dependent variable. Information quality measurement is a new measurement purposely constructed for this MIB_MeSys. Mobile Information Behavior Measuring System (MIB_MeSys) prototype offer a real time statistical data that enable library to understand their current user. Library may use data per item that presented to enhance digital library by focusing on the critical area.